The dilemma of green business in tropical forests: how to protect what it cannot identify - Meijaard, E.; Sheil, D. (Wiley, 2012)
Much tropical biodiversity resides in forests managed by timber, mining, and plantation companies. These companies can determine the local persistence of many species and have considerable implications for global conservation outcomes. Many companies are willing to invest in improved management as long as this does not undermine their business—indeed accessing green markets often makes commercial sense. Compliance with common standards of good commercial practice requires identification of all species of conservation significance which occur within their areas of management responsibility. But, as we demonstrate, it is impossible for companies to do this comprehensively. Such demands are often counterproductive in that they alienate those who might otherwise be willing to improve. Given the finite resources available for achieving conservation outcomes, we need to trade off data collection against other costs. To encourage adoption and implementation of conservation friendly practices requires incentives, not technical and financial obstacles. We challenge conservation biologists to reconsider the realities of good forest management, and provide pragmatic guidance for business compatible conservation. Until we engage more effectively with commercial interests, opportunities for improved conservation outcomes will be wasted.